A simple method for quick evaluation of the anterior tooth ratio: an observational study - Guanning Zhang; Qingchen Feng; Xiaoyu Wei; Ke Xing; Hongxiang Mei; Jiawei Zhou; Chen Jiang; Juan Li (BMC, 2022)
Abstract Background An ideal relationship of anterior teeth is closely related to postoperative function, stability, and aesthetics. Therefore, it is necessary to estimate the proportion of anterior teeth when communicating with patients about possible treatment plans and outcomes. This study aimed to establish a simple method for assessing the proportion of anterior teeth and to identify the standard ratio value to provide references for clinical work. Methods Five hundred fourteen patients were divided into derivation, standard, and validation datasets. We first deduced our novel simplified anterior tooth ratio (SATR) by finding the key teeth with the derivation datasets, then established standard values by measuring the standard models, and finally validated the diagnostic performance of SATR. Independent sample t-test was used to select key teeth. Pearson's correlation analysis and linear regression analysis was used to test and verify the correlation between SATR and the anterior Bolton ratio. Chi-square test and diagnostic test were used to verify the diagnostic results using SATR. P values of < 0.05 were considered statistically significant. Results Patients with an abnormal anterior Bolton ratio were more likely to have variations in the maxillary and mandibular lateral incisors. Therefore, the ratio of maxillary and mandibular lateral incisors was chosen as a simple way to assess the anterior tooth ratio and was defined as SATR (simplified anterior tooth ratio). A positive correlation was observed between SATR and anterior Bolton ratio (r = 0.702, p < 0.001), with the linear regression equation as follows: y = 0.503 + 0.328x, x = SATR, y = anterior Bolton ratio. The standard value of SATR was established (85.69% ± 3.57%) and proven reliable in clinical practice. Conclusions The ratio of maxillary and mandibular lateral incisors can be used to estimate the anterior tooth ratio, which showed high reliability and efficiency.